دور الأخصائي النفسي في إرشاد التلاميذ ذوي المشكلات السلوكية دراسة حالة وحدة الكشف والمتابعة أحمد زايد العالية بولاية بسكرة - ساعد, شفيق; بركات, نوال (دفـاتر المـــــــــــخبـر, 2018)
الملخص: نهدف من خلال هذه الدراسة إلى تشخيص دور الأخصائي النفسي في إرشادالتلاميذ ذوي المشكلات السلوكية، وذلك بالسعينحو تحليل المعطيات الكيفية والكمية للخدمات الإرشادية المقدمة لهؤلاء التلاميذ والتكفل بالتلاميذ المعنيين بالمتابعة التربوية والنفسية. وقد اعتمدنا على المنهج الوصفي التحليلي من خلال دراسة حالة وحدة الكشف والمتابعة أحمد زايد بالعالية الشرقية بولاية بسكرة، وشملت أدوات الدراسة استمارة مقابلة نصف موجهة تناولت محاور تهدف الإجابة على أسئلة الدراسة. Abstract: Educational counseling is an organized process that aims to help the student to understand his personality and know his abilities and solve his problems to achieve psychological and educational compatibility. The goal of this process is not only to address the difficulties in the educational process, but also to deal with different personal difficulties Among students, and among those difficulties may appear on the student of behavioral problems come in different forms and degrees and require the guide to deal directly with the student and his family and the parties to the educational process